Tax Avoidance And Firm Value: Unveiling The Role of Information Asymmetry - Fitriyani, Amanda; Rachmawati, Nurul Aisyah (Universitas Swadaya Gunung Jati, 2025)
In a market that is increasingly attentive to ethical and transparency issues, firms engaging in tax avoidance may face negative evaluations if they do not provide sufficient disclosure of information. Therefore, understanding the role of information asymmetry is crucial in explaining why the impact of tax avoidance on corporate value can vary under different conditions. This study aimed to examine the effect of tax avoidance on corporate value, with information asymmetry acting as a moderating variable. The population for this research included manufacturing companies listed on the Indonesia Stock Exchange from 2021 to 2023. Purposive sampling was used to select the sample. The data for this study were secondary data sourced from www.idx.co.id and https://finance.yahoo.com. The results showed that tax avoidance did not significantly affect corporate value; however, information asymmetry moderated the relationship between tax avoidance and corporate value. In this context, tax avoidance represents important information for investors when evaluating companies with high levels of information asymmetry.